Wnt signal-dependent antero-posterior specification of early-stage CNS primordia modeled in EpiSC-derived neural stem cells - Nakamura, Kae; Watanabe, Yusaku; Boitet, Claire; Satake, Sayaka; Iida, Hideaki; Yoshihi, Koya; Ishii, Yasuo; Kato, Kagayaki; Kondoh, Hisato (Frontiers in Cell and Developmental Biology, 2024)
The specification of the embryonic central nervous system (CNS) into future brain (forebrain, midbrain, or hindbrain) and spinal cord (SC) regions is a critical step of CNS development. A previous chicken embryo study indicated that anterior epiblast cells marked by Sox2 N2 enhancer activity are specified to the respective brain regions during the transition phase of the epiblast to the neural plate-forming neural primordium. The present study showed that the SC precursors positioned posterior to the hindbrain precursors in the anterior epiblast migrated posteriorly in contrast to the anterior migration of brain precursors. The anteroposterior specification of the CNS precursors occurs at an analogous time ( E7.5) in mouse embryos, in which an anterior-to-posterior incremental gradient of Wnt signal strength was observed. To examine the possible Wnt signal contribution to the anteroposterior CNS primordium specification, we utilized mouse epiblast stem cell (EpiSC)-derived neurogenesis in culture. EpiSCs maintained in an activin- and FGF2-containing medium start neural development after the removal of activin, following a day in a transitory state. We placed activin-free EpiSCs in EGF- and FGF2-containing medium to arrest neural development and expand the cells into neural stem cells (NSCs). Simultaneously, a Wnt antagonist or agonist was added to the culture, with the anticipation that different levels of Wnt signals would act on the transitory cells to specify CNS regionality; then, the Wnt-treated cells were expanded as NSCs. Gene expression profiles of six NSC lines were analyzed using microarrays and single-cell RNA-seq. The NSC lines demonstrated anteroposterior regional specification in response to increasing Wnt signal input levels: forebrain- midbrain-, hindbrain-, cervical SC-, and thoracic SC-like lines. The regional coverage of these NSC lines had a range; for instance, the XN1 line expressed Otx2 and En2, indicating midbrain characteristics, but additionally expressed the SC-characteristic Hoxa5. The ranges in the anteroposterior specification of neural primordia may be narrowed as neural development proceeds. The thoracic SC is presumably the posterior limit of the contribution by anterior epiblast-derived neural progenitors, as the characteristics of more posterior SC regions were not displayed.